Pengaruh Pendidikan Kesehatan Tentang HIV/AIDS Dengan Media Video Drama Dan Ceramah Terhadap Tingkat Pengetahuan Dan Sikap Remaja Dalam Pencegahan HIV/AIDS di SMA N 2 Boyolali - Setyawati, Dwi, Yuli Kusumawati, S.KM, M.Kes (Epid), Anisa Catur Wijayanti, SKM., M.Epid (2016)
AIDS is a syndrome or collection of symptoms due to the loss of one's immune. A survey of 10 student SMA N 2 Boyolali known to be less understood and rarely get a lesson on AIDS , and rarely get health counseling. This study aims to determine the effect of health education on HIV/AIDS with video drama to the level of knowledge and attitude of youth in HIV/AIDS prevention in high school N 2 Boyolali. This research method is True Experimental , with a pretest - posttest design with control group. The study population was all students of Class I and II SMA Negeri 2 Boyolali. The division of the sample in both groups using a randomization with 218 students sharing experimental group and the control group of 218 students. Analysis of the data used is a test of independent t test and Mann Whitney. The results showed the effect of health education on HIV / AIDS denganmedia video drama to the level of knowledge (P = 0.000) and the behavior of teenagers (P= 0.016) in the prevention of HIV/AIDS in high school N 2 Boyolali.